A ANALISIS STRATEGI KEPOLISIAN DAERAH ISTIMEWA YOGYAKARTA DALAM MENGATASI KEJAHATAN PENIPUAN ONLINE DI ERA SOCIETY 5.0 - Lukman Khakim; Nabila Nur Fadlilah (UNIB Press, 2024)
Online fraud is a crime in e-commerce using the internet. Online fraud crime is developing massively along with technological advances, giving rise to various modus operandi. This study aims to analyze and explain the strategies implemented by the Yogyakarta Special Region Police in overcoming the problem of online fraud crime in the era of society 5.0. This study uses an empirical legal research method with a field research approach. This study presents primary and secondary data taken from various sources, such as interviews with police officials and data related to online fraud cases. The results of the study show that the Yogyakarta Police in overcoming online fraud crimes in the era of society 5.0 has adopted various strategies, such as increasing public awareness, collaborating with digital platform providers, and improving digital investigation capabilities. However, challenges in dealing with online fraud remain, including legal constraints and technological lag. This research provides insight into how law enforcement is adapting to changes in the society 5.0 era and provides a basis for further improvements in efforts to address online fraud crimes.